PET (Polyethylene Terephthalate) master batch flame retardant, PET flame-retardant master batch and application
By using DOPO@Fe-BDC-NH2 as the PET masterbatch flame retardant, the flammability problem of PET fiber materials is solved, and the high-efficiency flame retardant performance of PET polyester materials is achieved, and the process is simple and suitable for industrial production.
Patent Information
- Application Number
- CN202510154658.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-04-22
AI Technical Summary
Due to the flammability of existing PET fiber materials, it is difficult to achieve industrial production in the fields of safety protective clothing, home textiles, etc., and the preparation of commonly used flame retardants is difficult to achieve industrial production.
DOPO@Fe-BDC-NH2 is used as the PET masterbatch flame retardant, and the MOF material Fe-BDC-NH2 is prepared by contacting and reacting the trivalent iron salt with 2-aminoterephthalic acid, and then reacting with DOPO to prepare the PET masterbatch flame retardant, and the PET flame retardant masterbatch is prepared by melt blending method.
The thermal stability and flame retardant properties of PET polyester materials are improved, the limit oxygen index reaches 28.4%, the vertical combustion level reaches V-0, and the preparation process is simple, which is suitable for industrial production.
Smart Images

Figure BDA0005269189100000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a PET masterbatch flame retardant, and also to a PET flame retardant masterbatch prepared by using the PET masterbatch flame retardant and application thereof. Background Art
[0002] Polyethylene terephthalate (PET) is widely used in chemical fiber, packaging, electronic appliances, medical and health care, construction, automobile and other fields due to its high strength and modulus, good elasticity, wear resistance and impact resistance. However, with the rapid development of the polyester industry chain and the continuous improvement of social living standards, conventional polyester fiber materials can no longer meet people's increasingly abundant practical needs. Limited by the chemical structure and combustion characteristics of PET fiber itself, its limiting oxygen index (LOI) is only about 21%, which is a flammable material, greatly limiting its application in safety protective clothing, home textiles and other fields. Therefore, the research and development of flame-retardant polyester materials is of great significance.
[0003] In recent years, with the demand brought by the development of green fibers, halogen-free and low-toxic flame retardants have received more and more attention. For example, Sun Ailin et al. used bio-based phytic acid as a ligand and ferric nitrate as a metal ion donor to prepare a metal organic framework flame retardant (Fe-MOF). Fe-MOF is amorphous, has good thermal stability, and a thermal decomposition temperature of 390°C. The composite flame-retardant polyester material (Fe-MOF-PET) prepared by melt blending, its SEM results show that Fe-MOF is uniformly loaded on the surface of the PET matrix; in the test, it was found that the addition of Fe-MOF had no obvious effect on the processing properties of PET, and the melting temperature remained at around 226°C; combustion tests and thermal analysis experiments showed that Fe-MOF-PET has certain smoke suppression and flame retardant effects. However, the preparation of this flame retardant is difficult and costly, and it is difficult to apply it in industrial production.
[0004] Therefore, studying a new type of PET masterbatch flame retardant and applying it to the preparation of flame retardant masterbatch will improve the flame retardant properties while simplifying the complicated preparation process, which will be beneficial to the industrial development of flame retardant polyester materials. Summary of the invention
[0005] The main technical problem solved by the present invention is to provide a PET masterbatch flame retardant, and also provide a PET flame retardant masterbatch prepared by using the PET masterbatch flame retardant and application thereof.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a PET masterbatch flame retardant, wherein the PET masterbatch flame retardant is a DOPO@Fe-BDC-NH2 flame retardant, which is prepared by a method comprising the following steps:
[0007] S1: contacting and reacting trivalent iron salt with 2-aminoterephthalic acid to obtain the MOF material Fe-BDC-NH2;
[0008] S2: DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) is contacted with the Fe-BDC-NH2 to obtain the PET masterbatch flame retardant.
[0009] As an embodiment of the present invention, the trivalent iron salt is ferric nitrate.
[0010] As an embodiment of the present invention, the trivalent iron salt is ferric nitrate nonahydrate (Fe(NO3)3·9H2O).
[0011] As an embodiment of the present invention, step S1 comprises:
[0012] S1-1: Mixing trivalent iron salt and 2-aminoterephthalic acid in a solvent, stirring to react, and producing white floccules;
[0013] S1-2: Adjust the pH value of the reaction system obtained in step S1-1 to 7.0-7.4, and then transfer it to a hydrothermal reactor for reaction at a reaction temperature of 95-100°C to obtain the MOF material Fe-BDC-NH2.
[0014] In step S1-1, the solvent is N,N-dimethylformamide (DMF).
[0015] As an embodiment of the present invention, step S2 comprises:
[0016] DOPO is added to the reaction solution obtained in step S1-2, and the temperature is raised to 120-123° C., followed by suction filtration, and the filter cake is dried to obtain the PET masterbatch flame retardant.
[0017] As an embodiment of the present invention, the filter cake is dried at 35-45° C. under vacuum.
[0018] As an embodiment of the present invention, the feed ratio of the ferric iron salt to the 2-aminoterephthalic acid is: Fe in the ferric iron salt 3+ The molar number of 2-aminoterephthalic acid is 1: (1.85-2.05). Specifically, Fe in the trivalent iron salt 3+ The molar number of 2-aminoterephthalic acid can be 1:1.85, 1:1.90, 1:1.95, 1:2.0, 1:2.05 or any other ratio within the range of 1:(1.85-2.05).
[0019] As an embodiment of the present invention, the feed ratio of the DOPO to the 2-aminoterephthalic acid is: the mole number of DOPO: the mole number of 2-aminoterephthalic acid is 1:(3.8-4.0). Specifically, the mole number of DOPO: the mole number of 2-aminoterephthalic acid can be 1:3.8, 1:3.9, 1:4.0 or any other ratio within the range of 1:(3.8-4.0).
[0020] The present invention also provides a PET flame retardant masterbatch, which is prepared by using the PET masterbatch flame retardant of the present invention.
[0021] As an embodiment of the present invention, the raw materials for preparing the PET flame retardant masterbatch include PET and a PET masterbatch flame retardant, and the mass percentage content of the PET masterbatch flame retardant is 0.5-5%. Specifically, in the raw materials for preparing the PET flame retardant masterbatch, the mass percentage content of the PET masterbatch flame retardant can be 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0% or other values within the range of 0.5-5%.
[0022] The present invention provides a method for preparing the PET flame retardant masterbatch of the present invention, which is prepared by a melt blending method, comprising the steps of:
[0023] Add DOPO@Fe-BDC-NH2 flame retardant into a pre-polycondensation reactor, add the esterified material obtained by PET esterification reaction into the pre-polycondensation reactor, and carry out mixed polycondensation reaction at a reaction temperature of 260-265° C. for a reaction time of 35-40 min to obtain a melt intermediate;
[0024] The obtained molten intermediate is transferred to a final polymerization reactor for curing to obtain PET flame retardant masterbatch.
[0025] The present invention further provides application of the PET flame retardant masterbatch of the present invention in preparing PET flame retardant material.
[0026] The intrinsic viscosity of the PET flame retardant masterbatch provided by the present invention is 0.648-0.667 dL / g, the terminal carboxyl content is 15.7-18.7 mol / t, the L value is ≥75, and the b value is 6.6-7.9. According to the test, the limiting oxygen index (LOI) of the PET flame retardant masterbatch provided by the present invention can reach 28.4%, and the vertical combustion grade (UL-94) can reach V-0 grade.
[0027] The present invention uses Fe as the central site and 2-aminoterephthalic acid (BDC-NH2) as an organic ligand to prepare a metal organic framework (MOF) material Fe-BDC-NH2, and then uses 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) to modify its surface to prepare a flame retardant DOPO@Fe-BDC-NH2, that is, a PET masterbatch flame retardant.
[0028] The PET masterbatch flame retardant was further melt-blended with the PET pre-condensation intermediate to prepare the Fe-MOF-PET flame retardant masterbatch. The flame retardant DOPO@Fe-BDC-NH2 can improve the thermal stability and flame retardancy of PET polyester materials. On the one hand, at higher temperatures, DOPO@Fe-BDC-NH2 can produce a stable covering layer on the surface of the polymer, making it difficult for the heat of combustion to enter the material, while isolating oxygen, thereby inhibiting the cracking of the polyester material; on the other hand, the flame retardant DOPO@Fe-BDC-NH2 can absorb the heat of the flame, reduce the thermal radiation formed by the flame on the surface of the material, and prevent the already vaporized combustible molecules from further cracking into free radicals, thus achieving a flame retardant effect.
[0029] The flame retardant masterbatch preparation method mentioned in the present invention is simple, and the prepared PET flame retardant masterbatch has excellent flame retardant properties.
[0030] The flame retardant masterbatch prepared by the present invention has a flame retardant evenly distributed in the PET matrix material, has no effect on the thermal stability of the PET matrix, and the melting temperature of the prepared flame retardant masterbatch is always maintained at 260-262° C. In the present invention, by loading DOPO on the surface of the metal organic framework (MOF) material Fe-BDC-NH2, the vapor phase flame retardant and condensed phase flame retardant properties of DOPO are utilized to further increase the flame retardant properties of the PET flame retardant masterbatch.
[0031] The PET masterbatch flame retardant provided by the present invention is low-toxic and halogen-free, and can meet the industry development needs of green polyester. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is described in detail below through specific embodiments. The following embodiments are intended to further illustrate the content of the present invention in detail, but are not intended to limit the scope of protection of the claims of the present invention.
[0033] In the following examples and comparative examples, the trivalent iron salt used is ferric nitrate nonahydrate (Fe(NO3)3·9H2O, purity 98.8%).
[0034] In the following examples and comparative examples, unless otherwise specified, all reagents used are commercially available products.
[0035] In the following examples and comparative examples, unless otherwise specified, the experimental methods used are conventional experimental methods.
[0036] Example 1
[0037] This embodiment provides a PET masterbatch flame retardant, and the preparation steps are as follows:
[0038] Weigh 84 kg of ferric nitrate nonahydrate (208 mol) and 73 kg of 2-aminoterephthalic acid (403 mol);
[0039] The weighed iron nitrate nine hydrate powder and 2-aminoterephthalic acid were placed in a stirring kettle, 400 kg of N, N-dimethylformamide (DMF) solvent was added to fully dissolve and fully stirred to produce white floccules, and the pH value of the reaction system was adjusted to neutral (pH value was 7.2) with sodium hydroxide solution, and then transferred to a hydrothermal kettle for reaction. The temperature of the hydrothermal kettle was controlled at 95-100 ° C and the reaction was carried out for 5 hours to obtain the MOF material Fe-BDC-NH2;
[0040] Then, 22 kg of DOPO (102 mol) was added to the reaction system, and the reaction liquid was heated to raise its temperature to 122° C., and filtered. The filter cake was dried under vacuum at 40° C. to obtain DOPO@Fe-BDC-NH2 flame retardant.
[0041] Example 2
[0042] This embodiment provides a PET masterbatch flame retardant, and the preparation steps are as follows:
[0043] Weigh 84 kg of ferric nitrate nonahydrate and 73 kg of 2-aminoterephthalic acid;
[0044] The weighed iron nitrate nine hydrate powder and 2-aminoterephthalic acid were placed in a stirring kettle, 400 kg of N, N-dimethylformamide (DMF) solvent was added to fully dissolve and fully stirred to produce white floccules, and the pH value of the reaction system was adjusted to neutral (pH value was 7.3) with sodium hydroxide solution, and then transferred to a hydrothermal kettle for reaction. The temperature of the hydrothermal kettle was controlled at 95-100 ° C and the reaction was carried out for 4 hours to obtain the MOF material Fe-BDC-NH2;
[0045] Then, 22 kg of DOPO was added to the reaction system, and the reaction liquid was heated to 120° C., and filtered. The filter cake was dried under vacuum at 40° C. to obtain DOPO@Fe-BDC-NH2 flame retardant.
[0046] Example 3
[0047] This embodiment provides a PET flame retardant masterbatch, which is prepared using the PET masterbatch flame retardant provided in Example 1. The preparation of the flame retardant masterbatch is carried out under a three-pot batch process, and the preparation steps are as follows:
[0048] Weigh 5 kg of the flame retardant DOPO@Fe-BDC-NH2 prepared in Example 1 and add it to the pre-polycondensation reactor in advance. After the PET esterification reaction is completed, transfer the esterified material to the pre-polycondensation reactor;
[0049] The polycondensation reaction is carried out in a pre-polycondensation reactor, the temperature in the reactor is controlled at 260-265°C, the reaction is carried out for 35 minutes, and then the molten intermediate is transferred to the final polymerization reactor, and cured according to the masterbatch curing process to obtain PET flame retardant masterbatch, and the discharge temperature of the final polymerization reactor is 285-285.5°C.
[0050] The PET flame retardant masterbatch prepared in this embodiment has a mass percentage content of 0.5% in the raw materials PET esterification material and PET masterbatch flame retardant.
[0051] Example 4
[0052] This embodiment provides a PET flame retardant masterbatch, which is prepared using the PET masterbatch flame retardant provided in Example 2. The preparation of the flame retardant masterbatch is carried out under a three-pot batch process, and the preparation steps are as follows:
[0053] Weigh 10 kg of the flame retardant DOPO@Fe-BDC-NH2 prepared in Example 2 and add it to the pre-polycondensation reactor in advance. After the PET esterification reaction is completed, transfer the esterified material to the pre-polycondensation reactor;
[0054] The polycondensation reaction is carried out in a pre-polycondensation reactor, the temperature in the reactor is controlled at 260-265°C, the reaction is carried out for 40 minutes, and then the molten intermediate is transferred to the final polymerization reactor, and cured according to the masterbatch curing process to obtain PET flame retardant masterbatch, and the discharge temperature of the final polymerization reactor is 285-285.5°C.
[0055] The PET flame retardant masterbatch prepared in this embodiment has a mass percentage content of 1.0% in the raw materials PET esterification material and PET masterbatch flame retardant.
[0056] Embodiment 5-8
[0057] Examples 5-8 respectively provide a PET flame retardant masterbatch, all of which are prepared using the PET masterbatch flame retardant provided in Example 2. The preparation steps refer to Example 4, with the only difference being that the prepared PET flame retardant masterbatch has different mass percentages of the PET masterbatch flame retardant in the preparation raw materials PET esterification material and PET masterbatch flame retardant. The specific contents are shown in Table 1 below.
[0058] Table 1
[0059]
[0060] Comparative Example 1
[0061] This comparative example provides a PET flame retardant masterbatch, and the preparation of the flame retardant masterbatch is carried out under a three-pot batch process, and the preparation steps are as follows:
[0062] Weigh 25 kg of flame retardant DOPO and add it to the pre-polycondensation reactor in advance. After the PET esterification reaction is completed, transfer the esterified material to the pre-polycondensation reactor;
[0063] The polycondensation reaction is carried out in a pre-polycondensation reactor, the temperature in the reactor is controlled at 260-265°C, the reaction is carried out for 40 minutes, and then the molten intermediate is transferred to the final polymerization reactor, and cured according to the masterbatch curing process to obtain PET flame retardant masterbatch, and the discharge temperature of the final polymerization reactor is 285-285.5°C.
[0064] The PET flame retardant masterbatch prepared in this comparative example has a mass percentage content of 2.5% in the raw materials PET esterification material and flame retardant DOPO.
[0065] Performance Testing
[0066] The PET flame retardant masterbatch prepared in the above Examples 3-8 and Comparative Example 1 was tested, and the test methods of the relevant performance indicators are as follows:
[0067] Intrinsic viscosity: measured in accordance with 5.1 of GB / T 14190-2017 Test method for fiber-grade polyester chips (PET); wherein the sample amount is 0.125±0.005g, the dissolution temperature is 110±10℃, and the constant temperature water bath temperature is 25.00±0.02℃.
[0068] L value: measured in accordance with GBT 14189-2015 "Fiber-grade polyester chips (PET)".
[0069] b value: measured in accordance with GBT 14189-2015 "Fiber-grade polyester chips (PET)".
[0070] Differential Scanning Calorimetry (DSC): The test was conducted using a DSC 1 differential scanning calorimeter from Mettler, Switzerland; an empty crucible was used as a reference, the nitrogen flow rate was controlled at 30 mL / min, and the temperature was increased from 25°C to 280°C at a heating rate of 10 K / min.
[0071] Thermogravimetric analysis (TG): The test was carried out using a 1 / 1100SF thermogravimetric analyzer from Mettler, Switzerland; the nitrogen flow rate was controlled at 30 mL / min, and the temperature was increased from 25°C to 680°C at a heating rate of 10 K / min.
[0072] Flame retardant performance test: According to the national standard GB / T2406-93 "Plastic Combustion Performance Test Method Oxygen Index Method", the limiting oxygen index of the flame retardant masterbatch is tested; according to the national standard GB2409-84 "Flame Retardant Performance Test Method-Vertical Burning Method", the vertical burning grade of the flame retardant masterbatch is tested.
[0073] The following are the test results of various embodiments and comparative examples.
[0074] The test results of the PET flame retardant masterbatch prepared in Example 3 are as follows:
[0075] The index analysis results of PET flame retardant masterbatch are: intrinsic viscosity is 0.651dL / g, terminal carboxyl content is 15.8mol / t, L value is 75, and b value is 6.6.
[0076] Thermal stability analysis: The initial thermal decomposition temperature of the ordinary PET masterbatch and the PET flame retardant masterbatch provided in Example 3 is about 355°C, and the maximum thermal weight loss temperature is around 396°C, which indicates that when the flame retardant addition amount is 0.5%, there is no significant effect on the thermal stability of the PET masterbatch. In addition, the residue of the ordinary PET masterbatch at 680°C accounts for about 1.11%, while the PET flame retardant masterbatch provided in Example 3 reaches 1.97%, which indicates that the addition of the flame retardant promotes the carbonization of the PET matrix during the combustion process. Analysis may be due to the catalytic effect of trivalent iron ions and the carbonization effect of DOPO.
[0077] Analysis of flame retardant properties: The limiting oxygen index (LOI value) of ordinary PET masterbatch is 20.9%, which is a flammable material. The limiting oxygen index of the PET flame retardant masterbatch provided in Example 3 reaches 26.5%. The vertical combustion level of ordinary PET masterbatch is V-2, and the PET flame retardant masterbatch provided in Example 3 is V-0. This shows that the addition of flame retardant DOPO@Fe-BDC-NH2 improves the flame retardant properties of PET masterbatch.
[0078] It should be noted that the common PET masterbatch in the present invention refers to a PET masterbatch prepared without adding any flame retardant, and the preparation process is as follows: after the PET esterification reaction is completed, the esterification material is transferred to a pre-polycondensation reactor, and a polycondensation reaction is carried out in the pre-polycondensation reactor. The temperature in the reactor is controlled at 260-265°C, and the reaction is carried out for 40 minutes. After that, the molten intermediate is transferred to a final polymerization reactor, and cured according to the masterbatch curing process to obtain a common PET masterbatch.
[0079] The test results of the PET flame retardant masterbatch prepared in Example 4 are as follows:
[0080] The analysis results of the PET flame retardant masterbatch indicators are as follows: the intrinsic viscosity is 0.649dL / g, the terminal carboxyl content is 15.7mol / t, the L value is 76, and the b value is 6.8.
[0081] Thermal stability analysis: The initial thermal decomposition temperature of PET flame retardant masterbatch is about 355°C, the maximum thermal weight loss temperature is around 396°C, and the residue at 680°C accounts for about 2.54%.
[0082] Flame retardant performance analysis: The limiting oxygen index of PET flame retardant masterbatch reaches 26.8%. The vertical combustion level of PET flame retardant masterbatch is V-0.
[0083] The test results of the PET flame retardant masterbatch prepared in Example 5 are as follows:
[0084] The analysis results of the PET flame retardant masterbatch indicators are as follows: the intrinsic viscosity is 0.653dL / g, the terminal carboxyl content is 15.7mol / t, the L value is 79, and the b value is 7.1.
[0085] Thermal stability analysis: The initial thermal decomposition temperature of PET flame retardant masterbatch is about 355°C, the maximum thermal weight loss temperature is around 396°C, and the residue at 680°C accounts for about 3.12%.
[0086] Flame retardant performance analysis: The limiting oxygen index of PET flame retardant masterbatch reaches 27.1%. The vertical combustion level of PET flame retardant masterbatch is V-0.
[0087] The test results of the PET flame retardant masterbatch prepared in Example 6 are as follows:
[0088] The analysis results of the PET flame retardant masterbatch indicators are as follows: the intrinsic viscosity is 0.653dL / g, the terminal carboxyl content is 16.1mol / t, the L value is 80, and the b value is 7.1.
[0089] Thermal stability analysis: The initial thermal decomposition temperature of PET flame retardant masterbatch is about 355°C, the maximum thermal weight loss temperature is around 397°C, and the residue at 680°C accounts for about 3.61%.
[0090] Flame retardant performance analysis: The limiting oxygen index of PET flame retardant masterbatch reaches 27.8%. The vertical combustion level of PET flame retardant masterbatch is V-0.
[0091] The test results of the PET flame retardant masterbatch prepared in Example 7 are as follows:
[0092] The analysis results of PET flame retardant masterbatch indicators are as follows: intrinsic viscosity is 0.653dL / g, terminal carboxyl content is 16.7mol / t, L value is 82, and b value is 7.3.
[0093] Thermal stability analysis: The initial thermal decomposition temperature of PET flame retardant masterbatch is about 355°C, the maximum thermal weight loss temperature is around 397°C, and the residue at 680°C accounts for about 4.12%.
[0094] Flame retardant performance analysis: The limiting oxygen index of PET flame retardant masterbatch reaches 28.4%. The vertical combustion level of PET flame retardant masterbatch is V-0.
[0095] The test results of the PET flame retardant masterbatch prepared in Example 8 are as follows:
[0096] The analysis results of the PET flame retardant masterbatch indicators are as follows: the intrinsic viscosity is 0.654dL / g, the terminal carboxyl content is 18.7mol / t, the L value is 82, and the b value is 7.9.
[0097] Thermal stability analysis: The initial thermal decomposition temperature of PET flame retardant masterbatch is about 355°C, the maximum thermal weight loss temperature is around 396°C, and the residue at 680°C accounts for about 5.07%.
[0098] Flame retardant performance analysis: The limiting oxygen index of PET flame retardant masterbatch reaches 26.3%. The vertical combustion level of PET flame retardant masterbatch is V-0.
[0099] The test results of the PET flame retardant masterbatch prepared in Comparative Example 1 are as follows:
[0100] The analysis results of PET flame retardant masterbatch indicators are as follows: intrinsic viscosity is 0.653dL / g, terminal carboxyl content is 16.3mol / t, L value is 81, and b value is 6.6.
[0101] Thermal stability analysis: The initial thermal decomposition temperature of PET flame retardant masterbatch is about 355°C, the maximum thermal weight loss temperature is around 396°C, and the residue at 680°C accounts for about 1.51%.
[0102] Flame retardant performance analysis: The limiting oxygen index of the PET flame retardant masterbatch reaches 27.6%. The vertical combustion level of the PET flame retardant masterbatch prepared in Comparative Example 1 is V-1 level.
[0103] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A PET masterbatch flame retardant, characterized in that: The PET masterbatch flame retardant is DOPO@Fe-BDC-NH2 flame retardant, which is prepared by a method comprising the following steps: S1: contacting and reacting trivalent iron salt with 2-aminoterephthalic acid to obtain the MOF material Fe-BDC-NH2; S2: DOPO is contacted with the Fe-BDC-NH2 to obtain the PET masterbatch flame retardant.
2. The PET masterbatch flame retardant according to claim 1, characterized in that: The trivalent iron salt is ferric nitrate.
3. The PET masterbatch flame retardant according to claim 2, characterized in that: The trivalent iron salt is ferric nitrate nonahydrate.
4. The PET masterbatch flame retardant according to any one of claims 1 to 3, characterized in that: The step S1 comprises: S1-1: Mix trivalent iron salt and 2-aminoterephthalic acid in a solvent, stir and react to produce white floccules; S1-2: Adjust the pH value of the reaction system obtained in step S1-1 to 7.0-7.4, and then transfer it to a hydrothermal reactor for reaction at a reaction temperature of 95-100°C to obtain the MOF material Fe-BDC-NH2.
5. The PET masterbatch flame retardant according to claim 4, characterized in that: The step S2 comprises: DOPO is added to the reaction solution obtained in step S1-2, and the temperature is raised to 120-123° C., followed by suction filtration, and the filter cake is dried to obtain the PET masterbatch flame retardant.
6. The PET masterbatch flame retardant according to claim 1, characterized in that: The feed ratio of the ferric iron salt to the 2-aminoterephthalic acid is: 3+ The number of moles of 2-aminoterephthalic acid is 1: (1.85-2.05); and / or, The feed ratio of the DOPO to the 2-aminoterephthalic acid is: the mole number of DOPO: the mole number of 2-aminoterephthalic acid is 1:(3.8-4.0).
7. A PET flame retardant masterbatch, prepared using the PET masterbatch flame retardant according to any one of claims 1 to 6.
8. The PET flame retardant masterbatch according to claim 7, characterized in that: The raw materials for preparing the PET flame retardant masterbatch include PET and a PET masterbatch flame retardant, and the content of the PET masterbatch flame retardant is 0.5-5wt%.
9. A method for preparing the PET flame retardant masterbatch according to claim 7 or 8, characterized in that: The preparation is carried out by a melt blending method, comprising the steps of: Add DOPO@Fe-BDC-NH2 flame retardant into a pre-polycondensation reactor, add the esterified material obtained by PET esterification reaction into the pre-polycondensation reactor, and carry out mixed polycondensation reaction at a reaction temperature of 260-265° C. for a reaction time of 35-40 min to obtain a melt intermediate; The obtained molten intermediate is transferred to a final polymerization reactor for curing to obtain PET flame retardant masterbatch.
10. Use of the PET flame retardant masterbatch according to claim 7 or 8 in the preparation of PET flame retardant materials.